Weed control in glyphosate-resistant corn grown in Manaus, Amazonas (Research, Society and Development, 2025)
Weeds cause reduced plant growth and yield in corn (Zea mays), forcing farmers to adopt control measures to reduce negative interference below the level of economic damage. Weed control with herbicides is the most widely used action, especially after the introduction of glyphosate-resistant cultivars. Thus, the objective of this study was to evaluate weed control in glyphosate-resistant corn grown on upland in Manaus, AM. The treatments evaluated were: 1- S-metolachlor 1,200 g; 2- S-metolachlor 1,200 g and hoeing 25 days after sowing (DAS); 3- S-metolachlor 1,200 g and glyphosate 1,440 g 25 DAS; 4- glyphosate 720 g 25 DAS; 5- glyphosate 1,080 g 25 DAS; 6- glyphosate 1,440 g 25 DAS; 7- hoeing 25 and 40 DAS; 8- check without weed control. The predominant weed species were Richardia brasiliensis and Rottboellia cochinchinensis. The average control efficiencies of R. cochinchinensis, R. brasiliensis and total weeds with glyphosate application were 93, 56 and 73%, respectively. The association of S-metolachlor and glyphosate promoted control efficacy of total weeds of 91%. The average grain yield obtained with isolated application of glyphosate was 9,236 kg ha-1 and significantly similar to those obtained in the other treatments with weed control. Weed control with glyphosate in corn resistant to this herbicide grown in Manaus was effective and made it possible to obtain yield equivalent to that obtained with two hoeings.